Prepreg, laminate, multilayer printed wiring board, semiconductor package, resin composition, and method for manufacturing prepreg, laminate, and multilayer printed wiring board

By using polyphenol derivatives with N-substituted maleimide structure and specific thermally cured resins in high-frequency electromagnetically compatible materials, the problem of insufficient high-frequency characteristics in the existing materials in the GHz range is solved, and the material's high adhesion, excellent thermal stability and low thermal expansion coefficient are achieved, meeting the multiple needs of modern electronic components for high frequency, thermal stability and fire safety.

JP7656422B2Active Publication Date: 2025-04-03RESONAC CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020505090
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-03-06
Filing Date
2019-03-06
Publication Date
2025-04-03
Estimated Expiration
2039-03-06

AI Technical Summary

Technical Problem

The existing high-frequency electromagnetic compatible materials have insufficient high-frequency characteristics in the GHz range and have high requirements for the adhesion, thermal expansion coefficient, fire safety and thermal stability of the conductor, but materials with these properties are difficult to achieve.

Method used

By adding polyphenol derivatives with N-substituted maleimide structure to the resin composition, and combining specific heat-curing resins and accelerators, the solid content and production process conditions of the resin are adjusted to prepare high-frequency electromagnetic compatible materials with high adhesion, excellent thermal stability and low thermal expansion coefficient.

Benefits of technology

It realizes materials with stable high-frequency characteristics in the GHz range, while improving adhesion, thermal stability and fire safety to conductors, meeting the requirements of electronic components with high density, high reliability and environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656422000001
    Figure 0007656422000001
  • Figure 0007656422000002
    Figure 0007656422000002
  • Figure 0007656422000003
    Figure 0007656422000003
Patent Text Reader

Abstract

The present invention provides a prepreg, a laminate, a multilayer printed wiring board, and a semiconductor package that are capable of exhibiting high adhesion to conductors, excellent heat resistance, a high glass transition temperature, a low coefficient of thermal expansion, flame retardancy, and stable, excellent high-frequency characteristics (dielectric characteristics in the high-frequency band). It also provides a resin composition that can provide the prepreg. It also provides methods for producing the prepreg, the laminate, and the multilayer printed wiring board. Specifically, the prepreg contains a resin composition and a sheet-like fiber-reinforced substrate, and generates less than 0.7% by mass of outgassing, based on the entire prepreg, when heated at 163°C for 15 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a prepreg, a laminate, a multilayer printed wiring board, a semiconductor package, and a resin composition, as well as methods for producing the prepreg, the laminate, and the multilayer printed wiring board. [Background technology]

[0002] The speed and capacity of signals used in mobile communication devices such as mobile phones, their base station equipment, network infrastructure devices such as servers and routers, and large computers are increasing year by year. Accordingly, printed wiring boards mounted on these electronic devices are required to be compatible with higher frequencies, and substrate materials with excellent dielectric properties (low dielectric constant and low dielectric tangent) (hereinafter sometimes referred to as high frequency properties) in high frequency bands that enable reduction in transmission loss are required. In recent years, in addition to the above-mentioned electronic devices, new systems that handle high frequency wireless signals have been put into practical use and planned for use in the ITS (Intelligent Transport Systems) field (related to automobiles and traffic systems) and in the field of indoor short-distance communication, as applications that handle such high frequency signals. It is expected that in the future, substrate materials with low transmission loss will be even more required for printed wiring boards mounted on these devices.

[0003] Furthermore, in light of recent environmental issues, there is a growing demand for the mounting of electronic components with lead-free solder and for halogen-free flame retardancy, so materials for printed wiring boards are required to have higher heat resistance and flame retardancy than ever before.

[0004] Conventionally, polyphenylene ether (PPE) resins have been used as heat-resistant thermoplastic polymers with excellent high-frequency characteristics in printed wiring boards that require low transmission loss. For example, a method of using polyphenylene ether and a thermosetting resin in combination has been proposed. Specifically, a resin composition containing polyphenylene ether and an epoxy resin (see, for example, Patent Document 1), a resin composition containing polyphenylene ether and a cyanate resin with a low dielectric constant among thermosetting resins (see, for example, Patent Document 2), and the like have been disclosed.

[0005] However, the resin compositions described in Patent Documents 1 and 2 above were generally insufficient in terms of high-frequency characteristics in the GHz range, adhesion to conductors, low thermal expansion coefficient, and flame retardancy, and had reduced heat resistance due to low compatibility between polyphenylene ether and thermosetting resins.

[0006] In order to solve such problems, the present inventors have proposed a resin composition (see, for example, Patent Document 3) that can improve compatibility, heat resistance, low thermal expansion coefficient, adhesion to conductors, etc. by forming a semi-IPN (semi-interpenetrating network) in the production stage (A stage) of a resin composition that contains an organic solvent and is based on a polyphenylene ether resin and a polybutadiene resin. However, in recent years, there has been a continuing need for substrate materials for printed wiring boards that have high adhesion to conductors, low thermal expansion coefficient, high glass transition temperature, high flame retardancy, etc., due to demands for high density, high reliability, and environmental compatibility in addition to compatibility with higher frequencies.

[0007] In addition, printed wiring board substrate materials used in network-related equipment applications such as servers and routers need to be highly multi-layered to meet the increasing density, and high reflow heat resistance and through-hole reliability are required. Furthermore, excellent dielectric properties are required in higher frequency bands as high-frequency characteristics, and while substrate materials generally show a tendency for the dielectric tangent to increase as the frequency increases, there is an increasing need to exhibit excellent dielectric properties in the 10 GHz band and above, rather than the conventional dielectric property values ​​in the 1 to 5 GHz range.

[0008] In order to solve these problems, the present inventors have proposed a resin composition (see Patent Document 4) that has good compatibility and can exhibit high frequency characteristics, high heat resistance, high adhesion to conductors, low thermal expansion characteristics, high flame retardancy, etc., by blending a polyphenylene ether derivative having a specific molecular structure with a specific thermosetting resin and a styrene-based thermoplastic elastomer. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 58-069046 [Patent Document 2] Special Publication No. 61-018937 [Patent Document 3] JP 2008-95061 A [Patent Document 4] International Publication No. 2016 / 175326 Summary of the Invention [Problem to be solved by the invention]

[0010] However, as a result of extensive research by the present inventors, it was found that even when conventional resin compositions were used, the high-frequency characteristics were sometimes inferior to those expected, and there was a need to develop a resin composition that would stably exhibit excellent high-frequency characteristics. In view of the current situation, the present invention has an object to provide a prepreg, a laminate, a multilayer printed wiring board, and a semiconductor package that are capable of exhibiting high adhesion to conductors, excellent heat resistance, a high glass transition temperature, a low thermal expansion coefficient, and flame retardancy, as well as stable and excellent high-frequency characteristics (dielectric characteristics in the high-frequency band); to provide a resin composition that can provide the prepreg; and to provide methods for producing the prepreg, the laminate, and the multilayer printed wiring board. [Means for solving the problem]

[0011] As a result of extensive research to solve the above problems, the inventors have discovered that in a resin composition containing a polyphenylene ether derivative having a specific molecular structure and an organic solvent, by adjusting the solids concentration to a predetermined value, it is possible to achieve stable and excellent high-frequency characteristics while maintaining high adhesion to conductors, excellent heat resistance, a high glass transition temperature, a low thermal expansion coefficient and flame retardancy, and have thus completed the present invention.

[0012] That is, the present invention relates to the following [1] to

[19] . [1] A prepreg comprising a resin composition and a sheet-like fiber reinforcing substrate, A prepreg that generates less than 0.7% by mass of outgas when heated at 163°C for 15 minutes, based on the entire prepreg. [2] The prepreg according to the above [1], wherein the resin composition contains a polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group. [3] The prepreg according to the above [2], wherein the N-substituted maleimide structure-containing group is a group containing a bismaleimide structure in which nitrogen atoms of two maleimide groups are bonded to each other via an organic group. [4] The resin composition according to the above [2] or [3], wherein the N-substituted maleimide structure-containing group is a group represented by the following general formula (Z): [ka] (In the formula, R 2 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. y is an integer of 0 to 4. 1 is a group represented by the following general formula (II), (III), (IV) or (V). [ka] (In the formula, R 3 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and p is an integer of 0 to 4. [ka] (In the formula, R 4 and R 5 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 2 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a single bond, or a group represented by the following general formula (III-1), and q and r each independently represent an integer of 0 to 4. [ka] (In the formula, R 6 and R 7 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 3 represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. Each of s and t is independently an integer of 0 to 4. [ka] (In the formula, n is an integer of 0 to 10.) [ka] (In the formula, R 8 and R 9 are each independently a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and u is an integer of 1 to 8. [5] The prepreg according to any one of the above [1] to [4], wherein the resin composition further contains at least one curing accelerator (B) selected from the group consisting of organic peroxides, imidazole-based curing accelerators, and phosphorus-based curing accelerators. [6] The prepreg according to any one of the above [1] to [5], wherein the resin composition further contains at least one thermosetting resin (C) selected from the group consisting of epoxy resins, cyanate resins, and maleimide compounds. [7] The prepreg according to the above item [6], wherein the maleimide compound in the thermosetting resin (C) comprises at least one selected from the group consisting of a maleimide compound (a) having at least two N-substituted maleimide structure-containing groups and an aminobismaleimide compound (c) represented by the following general formula (VI): [ka] (In the formula, A 4 is the A in the general formula (Z) described in [4] above. 1 is the same as the definition of A 5 is a group represented by the following general formula (VII). [ka] (In the formula, R 17 and R 18 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a hydroxyl group, or a halogen atom. 8 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a fluorenylene group, a single bond, or a group represented by the following general formula (VII-1) or (VII-2). q' and r' each independently represent an integer of 0 to 4. [ka] (In the formula, R 19 and R 20 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 9 represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an m- or p-phenylenediisopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. s' and t' each independently represent an integer of 0 to 4. [ka] (In the formula, R 21A is an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 10 and A 11 each independently represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond; and w is an integer of 0 to 4. [8] A laminate comprising the prepreg according to any one of the above [1] to [7] and a metal foil. [9] A multilayer printed wiring board comprising the prepreg according to any one of [1] to [7] above or the laminate according to [8] above.

[10] A semiconductor package comprising the multilayer printed wiring board according to [9] above and a semiconductor element mounted thereon.

[11] A resin composition comprising a polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group and an organic solvent, the resin composition having a solids concentration of 50.5 mass % or more.

[12] The resin composition according to the above

[11] , wherein the polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group has a structural unit represented by the following general formula (I): [ka] (In the formula, R 1 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and x is an integer of 0 to 4.

[13] The resin composition according to the above

[11] or

[12] , wherein the N-substituted maleimide structure-containing group is a group represented by the following general formula (Z): [ka] (In the formula, R 2 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. y is an integer of 0 to 4. 1 is a group represented by the following general formula (II), (III), (IV) or (V). [ka] (In the formula, R 3 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and p is an integer of 0 to 4. [ka] (In the formula, R 4 and R 5 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 2 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a single bond, or a group represented by the following general formula (III-1), and q and r each independently represent an integer of 0 to 4. [ka] (In the formula, R 6 and R 7 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 3 represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. Each of s and t is independently an integer of 0 to 4. [ka] (In the formula, n is an integer of 0 to 10.) [ka] (In the formula, R 8 and R 9 are each independently a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and u is an integer of 1 to 8.

[14] The resin composition according to any one of the above

[11] to

[13] , further comprising at least one curing accelerator (B) selected from the group consisting of organic peroxides, imidazole curing accelerators, and phosphorus curing accelerators.

[15] The resin composition according to any one of the above

[11] to

[14] , further comprising at least one thermosetting resin (C) selected from the group consisting of epoxy resins, cyanate resins and maleimide compounds.

[16] The resin composition according to the above

[15] , wherein the maleimide compound in the thermosetting resin (C) comprises at least one selected from the group consisting of a maleimide compound (a) having at least two N-substituted maleimide structure-containing groups and an aminobismaleimide compound (c) represented by the following general formula (VI): [ka] (In the formula, A 4 is the A in the general formula (Z) described in

[13] above. 1 is the same as the definition of A 5 is a group represented by the following general formula (VII). [ka] (In the formula, R 17 and R 18 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a hydroxyl group, or a halogen atom. 8 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a fluorenylene group, a single bond, or a group represented by the following general formula (VII-1) or (VII-2). q' and r' each independently represent an integer of 0 to 4. [ka] (In the formula, R 19 and R 20 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 9represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an m- or p-phenylenediisopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. s' and t' each independently represent an integer of 0 to 4. [ka] (In the formula, R 21 A is an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 10 and A 11 each independently represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond; and w is an integer of 0 to 4.

[17] A method for producing a prepreg, comprising impregnating or coating a sheet-shaped fiber-reinforced substrate with a resin composition and drying the substrate to produce a prepreg, the method comprising the step (X) of treating the prepreg so that the amount of outgassing satisfies the following condition: (Conditions for outgassing amount) The amount of outgassing generated when heated at 163°C for 15 minutes is less than 0.7% by mass based on the entire prepreg.

[18] A method for producing a laminate, comprising laminating a prepreg obtained by the method for producing a prepreg described in

[17] above and a metal foil, and applying heat and pressure by a pressing method.

[19] A method for producing a multilayer printed wiring board, comprising subjecting a prepreg obtained by the method for producing a prepreg described in

[17] above or a laminate obtained by the method for producing a laminate described in

[18] above to circuit formation processing and multilayer adhesion processing. Effect of the Invention

[0013] The present invention provides a prepreg, a laminate, a multilayer printed wiring board, and a semiconductor package that can exhibit high adhesion to a conductor, excellent heat resistance, a high glass transition temperature, a low coefficient of thermal expansion, and flame retardancy, as well as stable and excellent high-frequency characteristics (dielectric characteristics in a high-frequency band). Furthermore, a resin composition that can provide the prepreg can also be provided. Therefore, the resin composition, the prepreg, and the laminate can be suitably used for electronic component applications such as multilayer printed wiring boards and semiconductor packages. Furthermore, by using the method for producing a prepreg or the method for producing a laminate of the present invention to produce a multilayer printed wiring board, it is possible to produce a multilayer printed wiring board containing a laminate having high adhesion to a conductor, excellent heat resistance, a high glass transition temperature, a low coefficient of thermal expansion, flame retardancy, and excellent high-frequency characteristics (dielectric characteristics in the high frequency band). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the embodiments of the present invention will be described in detail. In this specification, a numerical range that is equal to or greater than X and equal to or less than Y (X and Y are real numbers) may be expressed as "X to Y." For example, the description "0.1 to 2" indicates a numerical range that is equal to or greater than 0.1 and equal to or less than 2, and the numerical range includes 0.1, 0.34, 1.03, 2, etc. In the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with the values ​​shown in the examples. In addition, the lower and upper limits of the numerical ranges may be arbitrarily combined with the lower or upper limit of other numerical ranges. The present invention also includes any combination of the features described in this specification.

[0015] [Prepreg] The present invention provides a prepreg containing a resin composition and a sheet-shaped fiber reinforcement substrate, which generates an amount of outgassing less than 0.7% by mass (more specifically, less than 0.70% by mass) based on the entire prepreg when heated at a temperature of 163° C. for 15 minutes (hereinafter sometimes referred to as “heat treatment for investigating the amount of outgassing”). The amount of outgassing is preferably 0.69% by mass or less, more preferably 0.67% by mass or less, even more preferably 0.65% by mass or less, particularly preferably 0.63% by mass or less, and most preferably 0.61% by mass or less based on the entire prepreg. The lower limit of the amount of outgassing is not particularly limited, but is often 0.1% by mass or more, may be 0.3% by mass or more, may be 0.4% by mass or more, or may be 0.45% by mass or more. In the present invention, the prepreg is not completely cured (C-staged) but is in a so-called semi-cured (B-staged) state. As a result of investigations by the present inventors, it was found that in order to obtain a laminate having excellent high-frequency characteristics while maintaining high adhesion to a conductor, excellent heat resistance, a high glass transition temperature, a low thermal expansion coefficient, and flame retardancy, it is important that the amount of outgassing from the prepreg is suppressed to the above-mentioned specific value, which led to the present invention.

[0016] One method for reducing the amount of outgassing from the prepreg of the present invention is (a) a method for adjusting the solid content concentration of the resin composition of the present invention to 50.5 mass % or more, or (b) a method for adjusting the drying conditions during production of the prepreg. It is preferable to adopt at least one method selected from the group consisting of these methods. In the present invention, the outgassing amount refers to the mass change rate determined from the mass of the prepreg before the heat treatment for investigating the outgassing amount (hereinafter may be abbreviated as the prepreg before heat treatment) and the mass of the prepreg after the heat treatment for investigating the outgassing amount (hereinafter may be abbreviated as the prepreg after heat treatment), and is calculated by the following formula. Outgassing amount (mass%)={(mass of prepreg before heat treatment-mass of prepreg after heat treatment) / mass of prepreg before heat treatment}×100 The outgas components are not particularly limited, but are thought to include at least one selected from the group consisting of organic solvents contained in the resin composition and raw materials mixed into each component of the resin composition.

[0017] (Prepreg manufacturing method) An example of a method for producing the prepreg of the present invention is a method for producing a prepreg by impregnating or coating a sheet-like fiber-reinforced substrate with a resin composition and drying the substrate, which includes a step (X) of treating the prepreg so that the outgassing amount thereof satisfies the condition that "the amount of outgassing generated when heated at a temperature of 163° C. for 15 minutes is less than 0.7% by mass based on the resin composition in the prepreg." The outgassing amount is as described above. The step (X) is not particularly limited as long as the outgassing amount of the prepreg falls within the above-mentioned range, and examples thereof include (a) a step of adjusting the solid content concentration of the resin composition of the present invention to 50.5 mass % or more [hereinafter, sometimes referred to as step (a)], and (b) a step of adjusting the drying conditions during the production of the prepreg [hereinafter, sometimes referred to as step (b)], etc. The solid content concentration of the resin composition in the step (a) will be described later. In the step (b), from the viewpoint of preventing the resin in the resin composition from decomposing, and keeping it in the B-stage rather than the C-stage, and further reducing the amount of outgassing, it is preferable to adopt drying conditions such as, for example, drying by heating at a temperature of preferably 80 to 200°C, more preferably 100 to 180°C, and even more preferably 120 to 170°C for preferably 1 to 30 minutes, more preferably 5 to 25 minutes, and even more preferably 10 to 20 minutes. The amount of the resin composition used is preferably adjusted so that the solid content derived from the resin composition in the dried prepreg is 30 to 90 mass% (the remainder corresponds to the content of the sheet-like fiber reinforcing substrate.) When the solid content derived from the resin composition in the dried prepreg is set within the above range to form a laminate, better moldability tends to be obtained.

[0018] As the sheet-like fiber reinforcement substrate of the prepreg, known ones used in various laminates for electrical insulating materials are used. Examples of the material of the sheet-like reinforcement substrate include inorganic fibers such as E glass, D glass, S glass, and Q glass; organic fibers such as polyimide, polyester, and tetrafluoroethylene; and mixtures thereof. These sheet-like reinforcement substrates have shapes such as woven fabric, nonwoven fabric, roving, chopped strand mat, and surfacing mat. In addition, the thickness of the sheet-like fiber reinforcement substrate is not particularly limited, and for example, a substrate having a thickness of 0.02 to 0.5 mm can be used. In addition, a substrate that has been surface-treated with a coupling agent or the like and a substrate that has been mechanically opened can be suitably used from the viewpoints of impregnation with the resin composition, heat resistance, moisture absorption resistance, and processability when made into a laminate. The resin composition contained in the prepreg will be described later.

[0019] As a method for impregnating or coating the sheet-like reinforcing substrate with the resin composition, a solvent method can be used. The solvent method is a method in which an organic solvent is added to a resin composition, a sheet-like reinforcing substrate is immersed in the obtained resin composition to impregnate the sheet-like reinforcing substrate with the resin composition, and then the substrate is dried.

[0020] [Resin composition] There is no particular limitation on the resin composition contained in the prepreg of the present invention, and any known resin composition utilized for insulating resin layers of printed wiring boards, etc., can be used. Among them, from the viewpoints of high adhesion to conductors, excellent heat resistance, high glass transition temperature, low thermal expansion coefficient, flame retardancy, and high frequency characteristics, a resin composition containing a polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group [hereinafter, sometimes simply referred to as polyphenylene ether derivative (A) or component (A)] is preferred. A preferred embodiment of the resin composition is a resin composition containing a polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group and an organic solvent, and having a solid content concentration of 50.5 mass % or more, from the viewpoint of obtaining excellent high-frequency characteristics while maintaining high adhesion to a conductor, excellent heat resistance, high glass transition temperature, low thermal expansion coefficient, and flame retardancy. When the resin composition of the present invention contains an inorganic filler (D) described later, the solid content concentration here refers to a solid content concentration including the inorganic filler. By setting the solid content concentration of the resin composition to 50.5 mass% or more, the high frequency characteristics tend to be stable and excellent compared to the case where the solid content concentration is less than 50.5 mass%. When the resin composition is impregnated or coated on a sheet-shaped fiber reinforced substrate to produce a prepreg, if the resin composition has low fluidity, the work becomes difficult, so in general, it is not desirable to increase the solid content concentration too much. Therefore, the solid content concentration is often adjusted to less than 50.5 mass%. However, when the solid content concentration of the resin composition containing the polyphenylene ether derivative (A) is intentionally increased to the above range, it was found that the organic solvent remaining in the laminate was reduced, which led to the suppression of the deterioration of the high frequency characteristics.

[0021] (Polyphenylene ether derivative (A)) The polyphenylene ether derivative (A) can be used without any particular limitation as long as it is a polyphenylene ether derivative having an N-substituted maleimide structure-containing group. The number of N-substituted maleimide structure-containing groups should be at least one.

[0022] In particular, the polyphenylene ether derivative (A) has an N-substituted maleimide structure-containing group, which results in a resin composition having excellent high-frequency characteristics, high adhesion to a conductor, high glass transition temperature, low thermal expansion coefficient, and high flame retardancy. Here, the thermal expansion coefficient in the present invention is a value also called the linear expansion coefficient. In addition, the N-substituted maleimide structure-containing group is not particularly limited as long as it contains an N-substituted maleimide group.

[0023] From the same viewpoint as above, the polyphenylene ether derivative (A) preferably has an N-substituted maleimide structure-containing group and a structural unit represented by the following general formula (I). [ka] (In the formula, R 1 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and x is an integer of 0 to 4.

[0024] R in the above general formula (I) 1 Examples of the aliphatic hydrocarbon group represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, and an n-pentyl group. The aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and is preferably a methyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. From the viewpoint of being halogen-free (reducing the content of chlorine atoms, bromine atoms, and iodine atoms), the halogen atom is preferably a fluorine atom. Among the above, R 1 is preferably an aliphatic hydrocarbon group having 1 to 5 carbon atoms.

[0025] x is an integer of 0 to 4, preferably an integer of 0 to 2, and more preferably 2. When x is 1 or 2, R 1 may be substituted at the ortho position on the benzene ring (based on the substitution position of the oxygen atom). When x is 2 or more, multiple R 1 They may be the same or different.

[0026] Specifically, the structural unit represented by the general formula (I) is preferably a structural unit represented by the following general formula (I'). [ka]

[0027] From the viewpoints of high frequency characteristics, adhesion to conductors, heat resistance, glass transition temperature, thermal expansion coefficient and flame retardancy, the N-substituted maleimide structure-containing group of the polyphenylene ether derivative (A) is preferably a group containing a bismaleimide structure in which the nitrogen atoms of two maleimide groups are bonded to each other via an organic group (however, structures derived from this structure are also included. Here, the structure derived from this structure is a structure in which the carbon-carbon double bond of the maleimide group reacts with a functional group (such as an amino group)). More preferably, it is a group represented by the following general formula (Z). [ka] (In the formula, R 2 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. y is an integer of 0 to 4. 1 is a group represented by general formula (II), (III), (IV) or (V) described later.

[0028] R 2 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R 1 This is explained in the same way as in the case of

[0029] y is an integer of 0 to 4, preferably an integer of 0 to 2, and more preferably 0. When y is an integer of 2 or more, a plurality of R 2 They may be the same or different.

[0030] A 1 The group represented by general formula (II), (III), (IV) or (V) is as follows. [ka]

[0031] (In the formula, R 3 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and p is an integer of 0 to 4. R 3The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R 1 This is explained in the same way as in the case of

[0032] p is an integer of 0 to 4, and from the viewpoint of availability, is preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0. When p is an integer of 2 or more, a plurality of R 3 They may be the same or different.

[0033] [ka] (In the formula, R 4 and R 5 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 2 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a single bond, or a group represented by the following general formula (III-1), and q and r each independently represent an integer of 0 to 4.

[0034] R 4 and R 5 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R 1 The aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and even more preferably an ethyl group.

[0035] A 2 Examples of the alkylene group having 1 to 5 carbon atoms represented by include a methylene group, a 1,2-dimethylene group, a 1,3-trimethylene group, a 1,4-tetramethylene group, a 1,5-pentamethylene group, etc. From the viewpoints of high frequency characteristics, adhesion to a conductor, heat resistance, glass transition temperature, thermal expansion coefficient, and flame retardancy, the alkylene group is preferably an alkylene group having 1 to 3 carbon atoms, and more preferably a methylene group.

[0036] A 2 Examples of the alkylidene group having 2 to 5 carbon atoms represented by include an ethylidene group, a propylidene group, an isopropylidene group, a butylidene group, an isobutylidene group, a pentylidene group, an isopentylidene group, etc. Among these, an isopropylidene group is preferred from the viewpoints of high frequency characteristics, adhesion to a conductor, heat resistance, glass transition temperature, thermal expansion coefficient, and flame retardancy. A 2 Among the above options, an alkylene group having 1 to 5 carbon atoms and an alkylidene group having 2 to 5 carbon atoms are preferable.

[0037] Each of q and r is independently an integer of 0 to 4. From the viewpoint of availability, each of them is preferably an integer of 0 to 2, and more preferably 0 or 2. When q or r is an integer of 2 or more, a plurality of R 4 R 5 They may be the same or different.

[0038] In addition, A 2 The group represented by the general formula (III-1) is as follows. [ka] (In the formula, R 6 and R 7 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 3 represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. Each of s and t is independently an integer of 0 to 4.

[0039] R 6 and R 7 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R 4 and R 5 This is explained in the same way as in the case of

[0040] A 3 The alkylene group having 1 to 5 carbon atoms represented by A2 Examples of the alkylene group include the alkylene group having 1 to 5 carbon atoms represented by the formula (I). A 3 Among the above options, an alkylidene group having 2 to 5 carbon atoms is preferable.

[0041] Each of s and t is an integer of 0 to 4. From the viewpoint of availability, each of them is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. When s or t is an integer of 2 or more, a plurality of R 6 R 7 They may be the same or different. [ka] (In the formula, n is an integer of 0 to 10.)

[0042] From the viewpoint of availability, n is preferably 0 to 5, and more preferably 0 to 3.

[0043] [ka] (In the formula, R 8 and R 9 are each independently a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms, and u is an integer of 1 to 8.

[0044] R 8 and R 9 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R 1 This is explained in the same way as in the case of u is an integer of 1 to 8, preferably an integer of 1 to 3, and more preferably 1.

[0045] A in the group represented by formula (Z) 1 From the viewpoints of high frequency characteristics, adhesion to a conductor, heat resistance, glass transition temperature, thermal expansion coefficient, and flame retardancy, it is preferable for the group to be a group represented by any one of the following formulas.

[0046] [ka]

[0047] A in the group represented by formula (Z) 1 From the viewpoints of high frequency characteristics, adhesion to a conductor, heat resistance, glass transition temperature, thermal expansion coefficient and flame retardancy, it is more preferable that the group be a group represented by any one of the following formulae. [ka]

[0048] The polyphenylene ether derivative (A) is preferably a polyphenylene ether derivative represented by the following general formula (A'). [ka] (In the formula, A 1 , R 1 , R 2 , x and y are as defined above, and m is an integer of 1 or more.

[0049] m is preferably an integer of 1 to 300, more preferably an integer of 10 to 300, further preferably an integer of 30 to 200, and particularly preferably an integer of 50 to 150.

[0050] The polyphenylene ether derivative (A) is preferably a polyphenylene ether derivative represented by any one of the following formulas (A'-1) to (A'-4).

[0051] [ka] (In the formula, m is the same as m in the general formula (A') above, and the preferred range is also the same.)

[0052] From the viewpoint of inexpensive raw materials, the polyphenylene ether derivative of the above formula (A'-1) is preferable, from the viewpoint of excellent dielectric properties and low water absorption, the polyphenylene ether derivative of the above formula (A'-2) is preferable, and from the viewpoint of excellent adhesion to the conductor and mechanical properties (elongation, breaking strength, etc.), the polyphenylene ether derivative of the above formula (A'-3) or (A'-4) is preferable. Therefore, according to the desired properties, one type of polyphenylene ether derivative represented by any one of the above formulas (A'-1) to (A'-4) can be used alone, or two or more types can be used in combination.

[0053] The number average molecular weight of the polyphenylene ether derivative (A) of the present invention is preferably 4,000 to 14,000, more preferably 5,000 to 12,000, further preferably 7,000 to 12,000, and particularly preferably 7,000 to 10,000. The number average molecular weight of the polyphenylene ether derivative (A) may be 4,000 to 8,000 or 4,000 to 6,500. If the number average molecular weight is 4,000 or more, the resin composition of the present invention, and the prepreg and laminate using the same tend to have a better glass transition temperature. If the number average molecular weight is 14,000 or less, the resin composition of the present invention tends to have a better moldability when used in a laminate. In this specification, the number average molecular weight is a value calculated from a calibration curve using standard polystyrene by gel permeation chromatography (GPC), and more specifically, a value determined by the method for measuring number average molecular weight described in the Examples.

[0054] The content of component (A) in the resin composition of the present invention is not particularly limited, but from the viewpoint of high-frequency characteristics, etc., it is preferably 1 mass % or more, more preferably 1 to 50 mass %, even more preferably 1 to 25 mass %, and particularly preferably 1 to 10 mass % based on the resin composition.

[0055] (Production method of polyphenylene ether derivative (A)) The polyphenylene ether derivative (A) can be obtained, for example, by the following production method. First, an aminophenol compound represented by the following general formula (VIII) [hereinafter referred to as aminophenol compound (VIII)] and, for example, a polyphenylene ether having a number average molecular weight of 15,000 to 25,000 are subjected to a known redistribution reaction in an organic solvent to produce a polyphenylene ether compound (A'') having a primary amino group (hereinafter also simply referred to as polyphenylene ether compound (A'')) while reducing the molecular weight of the polyphenylene ether. Next, the polyphenylene ether compound (A'') is subjected to a Michael addition reaction with a bismaleimide compound represented by the general formula (IX) [hereinafter referred to as bismaleimide compound (IX)] to produce a polyphenylene ether derivative (A).

[0056] [ka] (In the formula, R 2 and y are the same as those in the general formula (Z).

[0057] [ka] (In the formula, A 1 is the same as that in the general formula (Z).

[0058] Examples of the aminophenol compound (VIII) include o-aminophenol, m-aminophenol, p-aminophenol, etc. Among these, from the viewpoints of the reaction yield in producing the polyphenylene ether compound (A″) and the heat resistance in the resin composition, prepreg, and laminate, m-aminophenol and p-aminophenol are preferred, and p-aminophenol is more preferred.

[0059] The molecular weight of the polyphenylene ether compound (A'') can be controlled by the amount of the aminophenol compound (VIII) used. The larger the amount of the aminophenol compound (VIII) used, the lower the molecular weight of the resulting polyphenylene ether compound (A''). In other words, the amount of the aminophenol compound (VIII) used may be appropriately adjusted so that the number average molecular weight of the polyphenylene ether derivative (A) finally produced falls within a suitable range.

[0060] The amount of the aminophenol compound (VIII) to be blended is not particularly limited, but for example, if the polyphenylene ether to be reacted with the aminophenol compound (VIII) has a number average molecular weight of 15,000 to 25,000, then the compound can be used in an amount of 0.5 to 6 parts by mass per 100 parts by mass of the polyphenylene ether to obtain a polyphenylene ether derivative (A) having a number average molecular weight of 4,000 to 14,000.

[0061] The organic solvent used in the production process of the polyphenylene ether compound (A'') is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, butanol, butyl cellosolve, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and mesitylene; esters such as methoxyethyl acetate, ethoxyethyl acetate, butoxyethyl acetate, and ethyl acetate; and nitrogen-containing compounds such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. These may be used alone or in combination of two or more. Among these, toluene, xylene, and mesitylene are preferable from the viewpoint of solubility.

[0062] In addition, in the production process of the polyphenylene ether compound (A″), a reaction catalyst can be used as necessary. As the reaction catalyst, a reaction catalyst used in a known redistribution reaction can be used. For example, from the viewpoint of obtaining a polyphenylene ether compound (A″) having a stable number average molecular weight with good reproducibility, an organic peroxide such as t-butylperoxyisopropyl monocarbonate and a metal carboxylate such as manganese naphthenate may be used in combination. In addition, the amount of the reaction catalyst used is not particularly limited. For example, from the viewpoint of the reaction rate and gelation suppression in producing the polyphenylene ether compound (A″), the organic peroxide may be 0.5 to 5 parts by mass and the metal carboxylate may be 0.05 to 0.5 parts by mass relative to 100 parts by mass of the polyphenylene ether to be reacted with the aminophenol compound (VIII).

[0063] The aminophenol compound (VIII), the polyphenylene ether having a number average molecular weight of 15,000 to 25,000, an organic solvent, and optionally a reaction catalyst are charged in a reactor in predetermined amounts, and reacted while heating, keeping the temperature, and stirring to obtain a polyphenylene ether compound (A''). The reaction temperature and reaction time in this step can be those applied to reaction conditions for a known redistribution reaction. From the viewpoints of workability and suppression of gelation, and of being able to control the molecular weight of the polyphenylene ether compound (A″) to obtain the component (A) having a desired number average molecular weight, the reaction may be carried out, for example, at a reaction temperature of 70 to 110° C. for a reaction time of 1 to 8 hours.

[0064] The solution of the polyphenylene ether compound (A″) produced as described above may be continuously supplied as it is to the next step of producing a polyphenylene ether derivative (A). At this time, the solution of the polyphenylene ether compound (A″) may be cooled or adjusted to the reaction temperature of the next step. Furthermore, this solution may be concentrated as necessary to remove a part of the organic solvent, or may be diluted by adding an organic solvent, as described later.

[0065] Examples of the bismaleimide compound (IX) used in producing the polyphenylene ether derivative (A) include bis(4-maleimidophenyl)methane, polyphenylmethane maleimide, bis(4-maleimidophenyl)ether, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, m-phenylene bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, bis(4-maleimidophenyl)sulfone, bis(4-maleimidophenyl)sulfide, bis(4-maleimidophenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)sulfone, 4,4'-bis(3-maleimidophenoxy)biphenyl, and 1,6-bismaleimido-(2,2,4-trimethyl)hexane. These may be used alone or in combination of two or more.

[0066] Among these, from the viewpoints of high reactivity and higher heat resistance, bis(4-maleimidophenyl)methane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, and 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane are preferred.

[0067] From the viewpoints of being able to obtain polyphenylene ether derivatives including the polyphenylene ether derivative represented by the above formula (A'-1) and being inexpensive, bis(4-maleimidophenyl)methane is preferred. From the viewpoints of obtaining a polyphenylene ether derivative including the polyphenylene ether derivative represented by the formula (A'-2), excellent dielectric properties, and low water absorbency, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide is preferred. From the viewpoint of obtaining a polyphenylene ether derivative containing the formula (A'-3) or (A'-4) and having high adhesion to the conductor and excellent mechanical properties (elongation, breaking strength, etc.), 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane and 1,6-bismaleimido-(2,2,4-trimethyl)hexane may be used.

[0068] The amount of the bismaleimide compound (IX) used is determined by the amount of the aminophenol compound (VIII). That is, the equivalent ratio (Tb1 / Ta1) between the -NH2 group equivalent (Ta1) of the aminophenol compound (VIII) and the maleimide group equivalent (Tb1) of the bismaleimide compound (IX) may be in the range of 2 to 6, or may be in the range of 2 to 4. By using the bismaleimide compound (IX) within the above-mentioned equivalent ratio range, the resin composition, prepreg and laminate of the present invention tend to have better heat resistance, high glass transition temperature and high flame retardancy.

[0069] In the Michael addition reaction when producing the polyphenylene ether derivative (A), a reaction catalyst can be used as necessary. Examples of reaction catalysts that can be used include, but are not limited to, acid catalysts such as p-toluenesulfonic acid; amines such as triethylamine, pyridine, and tributylamine; imidazole compounds such as methylimidazole and phenylimidazole; and phosphorus catalysts such as triphenylphosphine. These may be used alone or in combination of two or more. The amount of the reaction catalyst is not particularly limited, but is preferably 0.01 to 5 parts by mass with respect to 100 parts by mass of the polyphenylene ether compound (A'').

[0070] The polyphenylene ether derivative (A) is obtained by charging the above-mentioned bismaleimide compound (IX) and, if necessary, a reaction catalyst and the like in a predetermined amount into a polyphenylene ether compound (A'') solution and carrying out a Michael addition reaction. This step is preferably carried out while heating, keeping warm, and stirring. From the viewpoint of workability and gelation inhibition, the reaction conditions are preferably, for example, a reaction temperature of 50 to 160°C and a reaction time in the range of 1 to 10 hours. In addition, in this step, the reaction concentration (solid content concentration) and the solution viscosity can be adjusted by adding or concentrating an organic solvent as described above. As the organic solvent to be additionally used, the organic solvents exemplified in the production step of the polyphenylene ether compound (A'') can be applied, and these may be used alone or in combination of two or more kinds. Among these, methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether, N,N-dimethylformamide, N,N-dimethylacetamide, and toluene are preferable from the viewpoint of solubility.

[0071] Furthermore, the reaction concentration (solid content concentration) in the production steps of the polyphenylene ether derivative (A) and the polyphenylene ether compound (A″) is not particularly limited, but is, for example, preferably 10 to 60 mass%, more preferably 20 to 50 mass% in both production steps. If the reaction concentration is 10 mass% or more, the reaction rate does not become too slow, and there is a tendency that it is more advantageous in terms of production costs. If the reaction concentration is 60 mass% or less, there is a tendency that better solubility can be obtained. In addition, there is a tendency that the solution viscosity is low, the stirring efficiency is good, and gelation is less likely to occur.

[0072] After the polyphenylene ether derivative (A) is produced, the solution may be concentrated by removing part or all of the organic solvent in the solution, or may be diluted by adding an organic solvent, depending on the workability when removing the polyphenylene ether derivative (A) from the reactor and the usage conditions when various thermosetting resins and the like are added to the polyphenylene ether derivative (A) to prepare the resin composition of the present invention (for example, the solution viscosity and solution concentration suitable for the production of a prepreg). There are no particular limitations on the organic solvent to be added, and one or more of the organic solvents described above can be used.

[0073] The formation of the polyphenylene ether compound (A'') and the polyphenylene ether derivative (A) obtained by the above-mentioned production steps can be confirmed by taking a small amount of a sample after the end of each step and subjecting it to GPC measurement and IR measurement. First, the polyphenylene ether compound (A'') has a lower molecular weight than the raw material polyphenylene ether by GPC measurement, and the peak of the raw material aminophenol compound (VIII) disappears. -1 The appearance of the primary amino group in the above-mentioned reaction mixture confirms that the desired polyphenylene ether compound (A'') has been produced. After purification by reprecipitation, the polyphenylene ether derivative (A) has a peak intensity of 3,300 to 3,500 cm from IR measurement. -1 The disappearance of the peak of the primary amino group and the peak of 1,700 to 1,730 cm -1 By confirming the appearance of a peak corresponding to the carbonyl group of maleimide, it can be confirmed that the desired polyphenylene ether derivative (A) has been produced.

[0074] The resin composition of the present invention tends to be superior in adhesion to a conductor, thermal expansion coefficient, flame retardancy, and processability (drilling and cutting) to a resin composition containing a polyphenylene ether compound (A″) and a component (C) described later.

[0075] (Organic solvent) From the viewpoints of dielectric properties, ease of handling, and ease of production of the prepreg described below, it is preferable that the resin composition of the present invention contains an organic solvent to adjust the solids concentration within the above range. The content of the organic solvent in the resin composition of the present invention is preferably adjusted so that the solid content concentration is 50.5% by mass or more from the viewpoint of high frequency characteristics. The solid content concentration of the resin composition is preferably 50.5 to 90% by mass, more preferably 51.0 to 80% by mass, more preferably 53.0 to 80% by mass, even more preferably 55.0 to 80% by mass, particularly preferably 55.0 to 75% by mass, and most preferably 55.0 to 70.0% by mass. By using a resin composition having a solid content concentration within the above range, it is possible to stably develop excellent high frequency characteristics, and the good high frequency characteristics can be further improved. In addition, the handling of the prepreg becomes easy, and the impregnation into the substrate and the appearance of the produced prepreg are good, and there is a tendency that the production of a prepreg with a desired thickness becomes easy. On the other hand, if the solid content concentration is less than 50.5% by mass, the organic solvent in the resin composition remains slightly in the prepreg, and the high frequency characteristics are slightly decreased. In order to meet the strong demand for high frequency characteristics in recent years, it is important to suppress this decrease in high frequency characteristics.

[0076] Examples of the organic solvent include alcohol-based solvents such as ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as tetrahydrofuran; aromatic solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; sulfur-containing solvents such as dimethyl sulfoxide; and ester-based solvents such as γ-butyrolactone. These may be used alone or in combination of two or more. Among these, from the viewpoint of solubility, alcohol-based solvents, ketone-based solvents, and aromatic solvents are preferred, and aromatic solvents are more preferred. More specifically, propylene glycol monomethyl ether and toluene are preferred.

[0077] (Cure accelerator (B)) In addition to the above-mentioned component (A), the resin composition of the present invention preferably contains at least one curing accelerator (B) selected from the group consisting of organic peroxides, imidazole curing accelerators, and phosphorus curing accelerators [hereinafter, sometimes simply referred to as curing accelerator (B) or component (B)]. By including component (B), the heat resistance and the like can be further improved.

[0078] The organic peroxide is not particularly limited, and examples thereof include methyl ethyl ketone peroxide, methyl acetoacetate peroxide, acetylacetonate peroxide, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(t-butylperoxy)butane, t-butyl hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, acetyl peroxide, octanoyl peroxide, lauroyl peroxide, benzoyl peroxide, m-toluyl peroxide, diisopropyl peroxydicarbonate, t-butylperoxyisopropyl monocarbonate, 1,1-di(t-hexyl peroxide), 1,2-di(t-butylperoxy)cyclohexane, ... Examples of the peroxy compounds include cyclohexane, t-butylene peroxybenzoate, n-butyl-4,4-di-(t-butylperoxy)valerate, p-menthane hydroperoxide, diisopropylbenzene, hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumin hydroperoxide, di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-hexyl peroxide, di-t-butyl peroxide, bis(1-phenyl-1-methylethyl)peroxide, and α,α'-bis(t-butylperoxy)diisopropylbenzene.

[0079] From the viewpoint of further improving heat resistance, it is preferable to contain, as the organic peroxide, at least one selected from the group consisting of t-butylperoxyisopropyl monocarbonate, 1,1-di(t-hexylperoxy)cyclohexane, bis(1-phenyl-1-methylethyl)peroxide, diisopropylbenzene hydroperoxide and α,α'-bis(t-butylperoxy)diisopropylbenzene.

[0080] From the viewpoints of storage stability and coatability, the organic peroxide preferably has a one-minute half-life temperature of 140° C. or higher, and more preferably 160° C. or higher. The one-minute half-life temperature can be determined by preparing a 0.1 mol / L organic peroxide solution in a solvent inactive to radicals such as benzene, thermally decomposing it in a nitrogen-substituted glass container, and measuring the temperature at which the amount of active oxygen is reduced to half in one minute.

[0081] Examples of the imidazole-based curing accelerator include imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 4,5-diphenylimidazole, 2-methylimidazoline, 2-phenylimidazoline, 2-undecylimidazoline, 2-heptadecylimidazoline, 2-isopropylimidazole, 2,4-dimethylimidazole, 2-phenyl-4-methylimidazole, 2-ethylimidazoline, 2-isopropylimidazoline, 2,4-dimethylimidazoline, and 2-phenyl-4-methylimidazoline.

[0082] From the viewpoint of storage stability of the resin composition, the imidazole-based curing accelerator is preferably a masked imidazole masked with a masking agent, such as acrylonitrile, phenylene diisocyanate, toluidine isocyanate, naphthalene diisocyanate, methylene bisphenyl isocyanate, melamine acrylate, and hexamethylene diisocyanate.

[0083] Examples of phosphorus-based curing accelerators include secondary amines such as morpholine, piperidine, pyrrolidine, dimethylamine, diethylamine, dicyclohexylamine, N-alkylarylamine, piperazine, diallylamine, thiazoline, and thiomorpholine; tertiary amines such as benzyldimethylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris(diaminomethyl)phenol; and quaternary ammonium salts such as tetrabutylammonium iodide, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium fluoride, benzalkonium chloride, benzyldi(2-hydroxyethyl)ethylammonium chloride, and decyldi(2-hydroxyethyl)methylammonium bromide.

[0084] The component (B) may be used alone or in combination of two or more types.

[0085] The content of component (B) is not particularly limited, but for example, it is preferably 0.01 to 25 parts by mass, more preferably 0.01 to 20 parts by mass, per 100 parts by mass of component (A) of the present invention (however, when component (C) described below is used, the total of components (A) and (C) is 100 parts by mass). When component (B) is used in such a range, better heat resistance and storage stability tend to be obtained.

[0086] (Thermosetting resin (C)) The resin composition of the present invention may contain, as component (C), at least one thermosetting resin selected from the group consisting of epoxy resins, cyanate resins, and maleimide compounds. The maleimide compounds do not include the polyphenylene ether derivative (A).

[0087] The epoxy resin is preferably an epoxy resin having two or more epoxy groups. Here, the epoxy resin is classified into glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, etc. Among these, glycidyl ether type epoxy resin may be selected.

[0088] Epoxy resins are classified into various epoxy resins according to the difference in the main skeleton, and within each of the above types of epoxy resins, they are further classified into bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, and bisphenol S type epoxy resins; alicyclic epoxy resins; aliphatic linear epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, and bisphenol F novolac type epoxy resins; phenol aralkyl type epoxy resins; stilbene type epoxy resins; dicyclopentadiene type epoxy resins; naphthalene skeleton-containing epoxy resins such as naphthol novolac type epoxy resins and naphthol aralkyl type epoxy resins; biphenyl type epoxy resins; biphenyl aralkyl type epoxy resins; xylylene type epoxy resins; dihydroanthracene type epoxy resins; dicyclopentadiene type epoxy resins, etc.

[0089] The epoxy resin may be used alone or in combination of two or more kinds. Among these, naphthalene skeleton-containing epoxy resins and biphenyl aralkyl epoxy resins are preferred from the viewpoints of high frequency characteristics, heat resistance, glass transition temperature, thermal expansion coefficient, flame retardancy, etc.

[0090] In addition, when an epoxy resin is used as the (C) component, a curing agent, a curing assistant, etc. for the epoxy resin can be used in combination as necessary. These are not particularly limited, but examples thereof include polyamine compounds such as diethylenetriamine, triethylenetetramine, diaminodiphenylmethane, m-phenylenediamine, and dicyandiamide; polyphenol compounds such as bisphenol A, phenol novolac resin, cresol novolac resin, bisphenol A novolac resin, and phenol aralkyl resin; acid anhydrides such as phthalic anhydride and pyromellitic anhydride; carboxylic acid compounds; and active ester compounds. These may be used alone or in combination of two or more. The amount used is not particularly limited and can be appropriately adjusted depending on the purpose. Among these, it is preferable to use polyphenol compounds and active ester compounds from the viewpoints of heat resistance, glass transition temperature, thermal expansion coefficient, storage stability, and insulation reliability.

[0091] The cyanate resin is not particularly limited, but examples thereof include 2,2-bis(4-cyanatophenyl)propane, bis(4-cyanatophenyl)ethane, bis(3,5-dimethyl-4-cyanatophenyl)methane, 2,2-bis(4-cyanatophenyl)-1,1,1,3,3,3-hexafluoropropane, α,α'-bis(4-cyanatophenyl)-m-diisopropylbenzene, cyanate compounds of phenol-added dicyclopentadiene polymers, phenol novolac type cyanate compounds, cresol novolac type cyanate compounds, etc. One type of cyanate resin may be used alone, or two or more types may be used in combination. Among these, it is preferable to use 2,2-bis(4-cyanatophenyl)propane from the viewpoint of production cost and the overall balance of high frequency characteristics and other characteristics.

[0092] In addition, when a cyanate resin is used as the (C) component, a curing agent, a curing assistant, etc. for the cyanate resin can be used in combination as necessary. These are not particularly limited, but examples thereof include monophenol compounds, polyphenol compounds, amine compounds, alcohol compounds, acid anhydrides, carboxylic acid compounds, etc. These may be used alone or in combination of two or more. The amount of the curing agent and the curing assistant used is not particularly limited, and can be appropriately adjusted depending on the purpose. Among these, it is preferable to use a monophenol compound from the viewpoints of high frequency characteristics, heat resistance, moisture absorption resistance, and storage stability.

[0093] When using a monophenol compound, it is preferable to use a method of pre-reacting the compound to form a phenol-modified cyanate prepolymer from the viewpoint of solubility in an organic solvent. The monophenol compound to be used in combination may be mixed in a specified amount when the compound is prepolymerized, or may be mixed in a specified amount before and after the compound is prepolymerized, but from the viewpoint of storage stability, a method of mixing the compound separately may be used.

[0094] The maleimide compound is not particularly limited, but may contain, for example, at least one of a maleimide compound (a) having at least two N-substituted maleimide structure-containing groups [hereinafter, sometimes referred to as component (a)] and an aminobismaleimide compound (c) represented by the following general formula (VI) [hereinafter, sometimes referred to as component (c)]. From the viewpoints of solubility in organic solvents, high-frequency characteristics, adhesion to conductors, and moldability of prepregs, the maleimide compound is preferably the aminobismaleimide compound (c).

[0095] The aminobismaleimide compound (c) can be obtained, for example, by subjecting the component (a) to a Michael addition reaction with an aromatic diamine compound (b) having two primary amino groups [hereinafter sometimes referred to as the component (b)] in an organic solvent.

[0096] [ka] (In the formula, A 4 is A in the general formula (Z). 1 is the same as the definition of A 5 is a group represented by the following general formula (VII).

[0097] [ka] (In the formula, R 17 and R 18 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a hydroxyl group, or a halogen atom. 8 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a fluorenylene group, a single bond, or a group represented by the following general formula (VII-1) or (VII-2). q' and r' each independently represent an integer of 0 to 4.

[0098] [ka] (In the formula, R 19 and R 20 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 9 represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an m- or p-phenylenediisopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. s' and t' each independently represent an integer of 0 to 4.

[0099] [ka] (In the formula, R 21 A is an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 10 and A 11each independently represents an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond; and w is an integer of 0 to 4.

[0100] R in the above general formula (VII), (VII-1) or (VII-2) 17 , R 18 , R 19 , R 20 and R 21 The aliphatic hydrocarbon group having 1 to 5 carbon atoms or the halogen atom represented by R in the general formula (I) is 1 The aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and is preferably a methyl group or an ethyl group.

[0101] A in the general formula (VII) or (VII-1) 8 and A 9 and the alkylene group having 1 to 5 carbon atoms and the alkylidene group having 2 to 5 carbon atoms represented by A in the general formula (VII-2). 10 and A 11 The alkylene group having 1 to 5 carbon atoms represented by A in the general formula (III) is 2 This is explained in the same way as in the case of

[0102] Each of q' and r' is an integer from 0 to 4, and from the viewpoint of availability, each is preferably an integer from 0 to 2, and preferably 0 or 2. Each of s' and t' is an integer from 0 to 4, and from the viewpoint of availability, each is preferably an integer from 0 to 2, and preferably 0 or 1, and preferably 0. Each of w is an integer from 0 to 4, and from the viewpoint of availability, each is preferably an integer from 0 to 2, and preferably 0.

[0103] The component (a) is not particularly limited, and may be the same as the bismaleimide compound (IX). Examples of the component (a) include bis(4-maleimidophenyl)methane, polyphenylmethane maleimide, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1,3-phenylene bismaleimide, m-phenylene bismaleimide, 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, bis(4-maleimidophenyl)sulfide, bis(4-maleimidophenyl)ketone, bis(4-(4-maleimidophenoxy)phenyl)sulfone, 4,4'-bis(3-maleimidophenoxy)biphenyl, and 1,6-bismaleimido-(2,2,4-trimethyl)hexane. The component (a) may be used alone or in combination of two or more depending on the purpose, application, etc. The component (a) is preferably a bismaleimide compound, and from the viewpoint of low cost, bis(4-maleimidophenyl)methane is preferable, from the viewpoint of excellent dielectric properties and low water absorption, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide is preferable, and from the viewpoint of high adhesion to the conductor and excellent mechanical properties (elongation, breaking strength, etc.), 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane is preferable.

[0104] As described above, the aminobismaleimide compound (c) can be obtained by subjecting the component (a) to a Michael addition reaction with the aromatic diamine compound (b) having two primary amino groups in an organic solvent.

[0105] The component (b) is not particularly limited, but from the viewpoints of high solubility in organic solvents, high reaction rate during synthesis, and high heat resistance, examples of the component (b) include 4,4'-diaminodiphenylmethane, 4,4'-diamino-3,3'-dimethyl-diphenylmethane, 4,4'-diamino-3,3'-diethyl-diphenylmethane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, and 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline. From the viewpoint of excellent solubility, reactivity, and heat resistance, as well as low cost, 4,4'-diaminodiphenylmethane, 4,4'-diamino-3,3'-dimethyl-diphenylmethane, and 4,4'-diamino-3,3'-diethyl-diphenylmethane are preferred. Also, from the viewpoint of excellent solubility, reactivity, and heat resistance, as well as the ability to exhibit high adhesion to a conductor, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, and 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline are preferred. Furthermore, in terms of excellent solubility, reactivity, heat resistance, and adhesion to conductors, as well as high-frequency characteristics and moisture absorption resistance, it is preferable to select 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline and 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline. These may be used alone or in combination of two or more depending on the purpose, application, etc.

[0106] The organic solvent used in producing the aminobismaleimide compound (c) is not particularly limited, and for example, the organic solvents exemplified in the production process of the polyphenylene ether compound (A'') can be used. These may be used alone or in combination of two or more. Among these, from the viewpoint of solubility, methyl ethyl ketone, cyclohexanone, propylene glycol monomethyl ether, N,N-dimethylformamide, and N,N-dimethylacetamide are preferable.

[0107] The amounts of the components (a) and (b) used when producing the component (c) are preferably such that the equivalent ratio (Tb2 / Ta2) of the -NH2 group equivalent (Ta2) of the component (b) to the maleimide group equivalent (Tb2) of the component (a) is in the range of 1 to 10, and more preferably in the range of 2 to 10. By using the components (a) and (b) within the above ranges, the resin composition, prepreg, and laminate of the present invention can achieve excellent high-frequency characteristics, high adhesion to conductors, excellent heat resistance, a high glass transition temperature, and high flame retardancy.

[0108] The reaction catalyst may not be used in the Michael addition reaction when producing the aminobismaleimide compound (c), but it can be used as necessary. The reaction catalyst is not particularly limited, but the reaction catalyst that can be used in the Michael addition reaction when producing the polyphenylene ether derivative (A) can be applied. The amount of the reaction catalyst is also not particularly limited as described above.

[0109] In addition, when a maleimide compound is used as the (C) component, a curing agent, a crosslinking agent, a curing assistant, etc. of the maleimide compound can be used in combination. These are not particularly limited, but examples thereof include vinyl compounds such as styrene monomer, divinylbenzene, and divinylbiphenyl; (meth)acrylate compounds; allyl compounds such as triallyl cyanurate and triallyl isocyanurate; and polyamine compounds such as diaminodiphenylmethane. These may be used alone or in combination of two or more. The amount of these used is not particularly limited, and can be appropriately adjusted depending on the purpose. Among these, vinyl compounds and polyamine compounds may be used from the viewpoint of high frequency characteristics and heat resistance.

[0110] The aminobismaleimide compound (c) is obtained by charging the above-mentioned components (a) and (b), an organic solvent, and, if necessary, a reaction catalyst, etc., in a reactor in predetermined amounts, and carrying out a Michael addition reaction while heating, keeping warm, and stirring. The reaction conditions in this step, such as the reaction temperature and reaction time, can be, for example, the reaction conditions in the Michael addition reaction in producing the polyphenylene ether derivative (A) described above.

[0111] The reaction concentration (solid content concentration) is not particularly limited, but is preferably 10 to 90% by mass, and more preferably 20 to 80% by mass. When the reaction concentration is 10% by mass or more, the reaction rate does not become too slow, and there is a tendency that it is more advantageous in terms of production costs. When the reaction concentration is 90% by mass or less, there is a tendency that better solubility is obtained. In addition, since the solution viscosity is low, the stirring efficiency is good and gelation is unlikely to occur. After the production of the aminobismaleimide compound (c), a part or all of the organic solvent can be removed (concentrated) or an organic solvent can be added to dilute the product according to the purpose, as in the production of the polyphenylene ether derivative (A).

[0112] (Content of component (A) and component (C)) When the resin composition of the present invention contains the (C) component, the content ratio of the (A) component to the (C) component [(A) / (C)] is not particularly limited, but is preferably 5 / 95 to 80 / 20, more preferably 5 / 95 to 75 / 25, more preferably 5 / 95 to 70 / 30, more preferably 5 / 95 to 50 / 50, and more preferably 10 / 90 to 50 / 50 in mass ratio. If the content ratio of the (A) component to the total of the (A) component and the (C) component is 5 mass% or more, better high frequency characteristics and low moisture absorption tend to be obtained. Also, if it is 80 mass% or less, better heat resistance, better moldability, and better processability tend to be obtained.

[0113] The thermosetting resin composition of the present invention may optionally contain an inorganic filler (D) (hereinafter sometimes referred to as component (D)) and a flame retardant (E) (hereinafter sometimes referred to as component (E)) as necessary. By including these, it is possible to further improve various properties when the composition is made into a laminate. For example, by including an appropriate inorganic filler in the thermosetting resin composition of the present invention, it is possible to improve low thermal expansion properties, high elastic modulus, heat resistance, flame retardancy, etc. In addition, by including an appropriate flame retardant, it is possible to impart high flame retardancy while suppressing the decrease in high frequency properties, heat resistance, adhesion to conductors, and glass transition temperature.

[0114] (Inorganic filler (D)) The component (D) used in the thermosetting resin composition of the present invention is not particularly limited, but for example, silica, alumina, titanium oxide, mica, beryllia, barium titanate, potassium titanate, strontium titanate, calcium titanate, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, clay such as calcined clay, talc, aluminum borate, silicon carbide, etc. can be used. These may be used alone or in combination of two or more. In addition, there is no particular limit to the shape and particle size of the inorganic filler, but for example, one having a particle size of 0.01 to 20 μm, preferably 0.1 to 10 μm, is suitably used. Here, the particle size refers to the average particle size, and is the particle size at the point corresponding to 50% volume when the cumulative frequency distribution curve of the particle size is calculated with the total volume of the particles being 100%. It can be measured by a particle size distribution measuring device using a laser diffraction scattering method.

[0115] When the (D) component is used, the amount of the component is not particularly limited, but for example, the content ratio of the (D) component in the thermosetting resin composition containing the (D) component is preferably 3 to 65% by volume, more preferably 5 to 60% by volume, and more preferably 10 to 60% by volume. When the content ratio of the (D) component in the entire thermosetting resin composition is within the above range, good curability, moldability, and chemical resistance can be obtained. When the (D) component is used, it is preferable to use a coupling agent in combination with the component in order to improve the dispersibility of the (D) component and the adhesion between the (D) component and the organic component in the resin composition. The coupling agent is not particularly limited, and for example, various silane coupling agents and titanate coupling agents can be used. These may be used alone or in combination of two or more. The amount of the component is not particularly limited, and it is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the (D) component used. Within this range, the deterioration of various properties is minimal, and the advantages of using the above-mentioned component (D) can be effectively exhibited. When using a coupling agent, it is preferable to use an inorganic filler that has been surface-treated in advance with a coupling agent by a dry or wet method, rather than the so-called integral blending method in which the coupling agent is added after blending the component (D) in the resin composition. By using this method, the advantages of the above-mentioned component (D) can be more effectively exhibited.

[0116] In the present invention, when the component (D) is used, it is more preferable to use the component (D) as a slurry in which the component (D) is previously dispersed in an organic solvent, as necessary, in order to improve the dispersibility of the component (D) in the thermosetting resin composition. The organic solvent used when forming the component (D) into a slurry is not particularly limited, but the organic solvents exemplified in the above-mentioned manufacturing process of the polyphenylene ether compound (A') can be applied. These may be used alone or in combination of two or more. Among these, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone are preferable from the viewpoint of dispersibility. The non-volatile content concentration of the slurry is not particularly limited, but is preferably 50 to 80 mass %, more preferably 60 to 80 mass %, from the viewpoint of sedimentation and dispersibility of the inorganic filler.

[0117] (Flame retardant (E)) The resin composition of the present invention may contain a flame retardant (E). Examples of the (E) component include phosphorus-based flame retardants, metal hydrates, and halogen-based flame retardants. From the viewpoint of environmental issues, the (E) component is preferably at least one selected from the group consisting of phosphorus-based flame retardants and metal hydrates, and more preferably a phosphorus-based flame retardant and a metal hydrate are used in combination. The (E) flame retardant may be used alone or in combination of two or more.

[0118] - Phosphorus-based flame retardants - The phosphorus-based flame retardant is not particularly limited as long as it contains phosphorus atoms among those generally used as flame retardants, and is preferably an inorganic phosphorus-based flame retardant or an organic phosphorus-based flame retardant. From the viewpoint of environmental issues, it is possible to select one that does not contain halogen atoms. From the viewpoints of high frequency characteristics, adhesion to conductors, heat resistance, glass transition temperature, thermal expansion coefficient, and flame retardancy, it is preferable to use an organic phosphorus-based flame retardant.

[0119] Examples of inorganic phosphorus-based flame retardants include red phosphorus; ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate; inorganic nitrogen-containing phosphorus compounds such as phosphoric acid amide; phosphoric acid; and phosphine oxide.

[0120] Examples of organic phosphorus-based flame retardants include aromatic phosphate esters, mono-substituted phosphonic acid diesters, di-substituted phosphinic acid esters, metal salts of di-substituted phosphinic acid, organic nitrogen-containing phosphorus compounds, and cyclic organic phosphorus compounds. Among these, aromatic phosphate ester compounds and metal salts of di-substituted phosphinic acid can be selected. Here, the metal salt is preferably any one of lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts, aluminum salts, titanium salts, and zinc salts, and is preferably an aluminum salt. Among organic phosphorus-based flame retardants, aromatic phosphate esters can be selected.

[0121] Examples of aromatic phosphate esters include triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, cresyl di-2,6-xylenyl phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di-2,6-xylenyl phosphate), bisphenol A bis(diphenyl phosphate), and 1,3-phenylene bis(diphenyl phosphate).

[0122] Examples of the mono-substituted phosphonic acid diester include divinyl phenylphosphonate, diallyl phenylphosphonate, and bis(1-butenyl) phenylphosphonate. Examples of the disubstituted phosphinate ester include phenyl diphenylphosphinate and methyl diphenylphosphinate. Examples of the metal salt of disubstituted phosphinic acid include metal salts of dialkylphosphinic acid, metal salts of diallylphosphinic acid, metal salts of divinylphosphinic acid, metal salts of diarylphosphinic acid, etc. These metal salts are preferably any one of lithium salt, sodium salt, potassium salt, calcium salt, magnesium salt, aluminum salt, titanium salt, and zinc salt, and more preferably aluminum salt.

[0123] Examples of the organic nitrogen-containing phosphorus compound include phosphazene compounds such as bis(2-allylphenoxy)phosphazene and dicresylphosphazene; melamine phosphate; melamine pyrophosphate; melamine polyphosphate; and melam polyphosphate.

[0124] Examples of the cyclic organic phosphorus compound include 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and the like.

[0125] Among these, at least one selected from the group consisting of aromatic phosphate esters, metal salts of disubstituted phosphinic acids, and cyclic organic phosphorus compounds is preferred, at least one selected from the group consisting of metal salts of disubstituted phosphinic acids and cyclic organic phosphorus compounds is more preferred, and it is even more preferred to use a metal salt of disubstituted phosphinic acids and a cyclic organic phosphorus compound in combination. In particular, the metal salt of disubstituted phosphinic acids is preferably a metal salt of dialkylphosphinic acids, and more preferably an aluminum salt of dialkylphosphinic acids. The cyclic organic phosphorus compound is preferably 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0126] In addition, when a metal salt of a di-substituted phosphinic acid and a cyclic organophosphorus compound are used in combination, the content ratio of the metal salt of a di-substituted phosphinic acid to the cyclic organophosphorus compound [metal salt of a di-substituted phosphinic acid / cyclic organophosphorus compound], in mass ratio, is preferably 0.6 to 2.5, more preferably 0.9 to 2, still more preferably 1 to 2, and still more preferably 1.2 to 2.

[0127] The aromatic phosphate ester is preferably an aromatic phosphate ester represented by the following general formula (E-1) or (E-2), and the metal salt of the di-substituted phosphinic acid is preferably a metal salt of a di-substituted phosphinic acid represented by the following general formula (E-3).

[0128] [ka]

[0129] (In the formula, R E1 ~R E5 each independently represents an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. e and f each independently represent an integer of 0 to 5, and g, h and i each independently represent an integer of 0 to 4. R E6 and R E7 are each independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or an aromatic hydrocarbon group having 6 to 14 carbon atoms. M is a lithium atom, a sodium atom, a potassium atom, a calcium atom, a magnesium atom, an aluminum atom, a titanium atom, or a zinc atom. m1 is an integer of 1 to 4.

[0130] R E1 ~R E5 The aliphatic hydrocarbon group having 1 to 5 carbon atoms and the halogen atom represented by R in the above general formula (I) are 1 The same things can be said as in the case of

[0131] Each of e and f is preferably an integer of 0 to 2, and preferably 2. Each of g, h and i is preferably an integer of 0 to 2, and preferably 0 or 1, and preferably 0.

[0132] R E6 and R E7 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R 1 The aliphatic hydrocarbon group is preferably an aliphatic hydrocarbon group having 1 to 3 carbon atoms, and is preferably an ethyl group.

[0133] R E6 and R E7 Examples of the aromatic hydrocarbon group having 6 to 14 carbon atoms represented by include a phenyl group, a naphthyl group, a biphenylyl group, an anthryl group, etc. The aromatic hydrocarbon group is preferably an aromatic hydrocarbon group having 6 to 10 carbon atoms.

[0134] m1 represents the valence of the metal ion, that is, it varies within the range of 1 to 4 depending on the type of M. M is preferably an aluminum atom. When M is an aluminum atom, m1 is 3.

[0135] -Metal hydrate- Examples of metal hydrates include aluminum hydroxide hydrates and magnesium hydroxide hydrates. These may be used alone or in combination of two or more. The metal hydroxides may also be inorganic fillers, but are classified as flame retardants when they are materials that can impart flame retardancy.

[0136] -Halogen-based flame retardants- Examples of halogen-based flame retardants include chlorine-based flame retardants and bromine-based flame retardants. Examples of chlorine-based flame retardants include chlorinated paraffin. Examples of bromine-based flame retardants include brominated epoxy resins such as brominated bisphenol A type epoxy resins and brominated phenol novolac type epoxy resins; hexabromobenzene, pentabromotoluene, ethylene bis(pentabromophenyl), ethylene bistetrabromophthalimide, 1,2-dibromo-4-(1,2-dibromoethyl)cyclohexane, tetrabromocyclooctane, hexabromocyclododecane, bis(tribromophenoxy)ethane, brominated polyphenylene ether, brominated polystyrene, 2,4,6-tris(tribromophenoxy)- Examples of such flame retardants include bromine-additive flame retardants such as 1,3,5-triazine (here, "additive type" refers to bromine introduced into the polymer in a form that is not chemically bonded, i.e., blended); and bromination reaction type flame retardants containing unsaturated double bond groups, such as tribromophenylmaleimide, tribromophenylacrylate, tribromophenylmethacrylate, tetrabromobisphenol A type dimethacrylate, pentabromobenzyl acrylate, and brominated styrene (here, "reactive type" refers to bromine introduced into the polymer in a form that is chemically bonded). These may be used alone or in combination of two or more.

[0137] (Content of component (E)) When the resin composition of the present invention contains a phosphorus-based flame retardant, the content ratio of the phosphorus-based flame retardant in the resin composition of the present invention is not particularly limited, but for example, the content of phosphorus atoms in the resin composition (total of other components excluding the component (D)) converted into solid content is preferably 0.2 to 5 mass%, more preferably 0.3 to 3 mass%. When the content of phosphorus atoms is 0.2 mass% or more, better flame retardancy tends to be obtained. Also, when the content of phosphorus atoms is 5 mass% or less, better moldability, high adhesion to conductors, excellent heat resistance, and high glass transition temperature tend to be obtained.

[0138] On the other hand, when a halogen-based flame retardant is contained in the resin composition of the present invention, the content thereof is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the total of the components (A) and (C) (however, if the component (C) is not used, then the content is 100 parts by mass of the component (A)), from the viewpoints of environmental issues and chemical resistance.

[0139] Furthermore, when a flame retardant other than the phosphorus-based flame retardant and the halogen-based flame retardant is contained in the resin composition of the present invention, the amount is not particularly limited, but is preferably 0.5 to 20 parts by mass, more preferably 1 to 15 parts by mass, more preferably 1 to 10 parts by mass, and even more preferably 1 to 6 parts by mass, relative to 100 parts by mass of the total of the (A) component and the (C) component (however, when the (C) component is not used, 100 parts by mass of the (A) component).

[0140] (Flame retardant assistant) The resin composition of the present invention may contain a flame retardant auxiliary, such as inorganic flame retardant auxiliary such as antimony trioxide or zinc molybdate.

[0141] When the resin composition of the present invention contains a flame retardant auxiliary, the content is not particularly limited, but for example, it is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 10 parts by mass, per 100 parts by mass of the total of the (A) and (C) components (however, when the (C) component is not used, the (A) component is 100 parts by mass). When the flame retardant auxiliary is used in such a range, better chemical resistance tends to be obtained.

[0142] The resin composition of the present invention may contain, as necessary, a coupling agent, an antioxidant, a heat stabilizer, an antistatic agent, an ultraviolet absorber, a pigment, a colorant, a lubricant, etc., which are appropriately selected. These may be used alone or in combination of two or more. The amount of these to be used is not particularly limited. Although not particularly limited, one embodiment of the resin composition of the present invention is one that does not substantially contain a thermoplastic elastomer. Here, "substantially does not contain" includes 0 parts by mass, i.e., no thermoplastic elastomer is contained, or the amount of the thermoplastic elastomer that is contained to an extent that is essentially meaningless (for example, in the case of a thermoplastic elastomer, 1 part by mass or less, 0.5 parts by mass or less, etc.). Examples of the thermoplastic elastomer include styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, polyester-based elastomers, polyamide-based elastomers, acrylic-based elastomers, silicone-based elastomers, and derivatives thereof.

[0143] (Method of producing resin composition) The resin composition can be produced by mixing the (A) component, the (B) component, the (C) component, other components, organic solvent, etc., which are contained as necessary, by a known method. At this time, dissolution or dispersion may be performed while stirring. The mixing order, temperature and time during mixing and stirring are not particularly limited and can be set as desired. As described above, when producing the resin composition of the present invention, by adjusting the solid content concentration of the resin composition to the above range, it tends to be easy to obtain a laminate having excellent high frequency characteristics. Therefore, the method for producing the resin composition preferably has a "solid content concentration adjustment step of adjusting the solid content concentration of the resin composition containing the polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group and an organic solvent to 50.5 mass% or more." The resin composition used in the solid content concentration adjustment step is as described above regarding the resin composition.

[0144] (Physical properties or characteristics) When a laminate is produced from the resin composition of the present invention, the glass transition temperature of the cured product of the resin composition is not particularly limited, but from the viewpoint of good heat resistance and through-hole connection reliability, as well as excellent processability in manufacturing electronic components, etc., the glass transition temperature of the resin composition after curing is preferably 150° C. or higher, more preferably 160° C. or higher, even more preferably 170° C. or higher, particularly preferably 180° C. or higher, and most preferably 200° C. or higher. There is no particular upper limit to the glass transition temperature, but it is preferably 1,000° C. or lower, preferably 500° C. or lower, and preferably 300° C. or lower, for example.

[0145] In addition, when a laminate is produced from the resin composition of the present invention, the thermal expansion coefficient (Z direction, Tg or less) of the cured product of the resin composition is not particularly limited, but from the viewpoint of suppressing warping of the laminate, it is preferably 57 ppm / ° C. or less, more preferably 50 ppm / ° C. or less, even more preferably 45 ppm / ° C. or less, and particularly preferably 40 ppm / ° C. or less. There is no limit to the lower limit of the thermal expansion coefficient, but it is, for example, 25 ppm / ° C. or more. The glass transition temperature and the thermal expansion coefficient are values ​​measured in accordance with the IPC standard, as described in the examples.

[0146] When a laminate is produced from the resin composition of the present invention, the dielectric constant and dielectric loss tangent of the cured product of the resin composition are not particularly limited, but from the viewpoint of suitable use in the high frequency band, it is preferable that the dielectric constant at 10 GHz is small, specifically, it is preferably 3.85 or less, more preferably 3.70 or less, and even more preferably 3.60 or less. There is no particular limit to the lower limit of the dielectric constant, but it is, for example, 0.5 or more, may be 1.0 or more, may be 3.0 or more, or may be 3.4 or more.

[0147] In addition, it is preferable that the dielectric loss tangent at 10 GHz is small, specifically, it is preferably 0.007 or less, more preferably 0.006 or less, and further preferably 0.0055 or less. There is no particular restriction on the lower limit of the dielectric loss tangent, and the smaller the better, but it is, for example, 0.0001 or more, may be 0.0020 or more, or may be 0.0040 or more. The dielectric constant and dielectric loss tangent are values ​​measured by the cavity resonator method as in the examples. Thus, the resin composition, prepreg, laminate, and multilayer printed wiring board of the present invention can be suitably used in electronic devices that handle high-frequency signals of 1 GHz or more, and can be particularly suitably used in electronic devices that handle high-frequency signals of 10 GHz or more or high-frequency signals of 30 GHz or more.

[0148] [Laminates and multilayer printed wiring boards and their manufacturing methods] The laminate of the present invention is a laminate containing the prepreg of the present invention and a metal foil. The laminate of the present invention can be produced, for example, by laminating the prepreg obtained by the prepreg production method of the present invention and a metal foil, and curing the laminate by heating and pressing using a press method. More specifically, the laminate can be produced by disposing a metal plate on one or both sides of a single prepreg of the present invention, or disposing a metal foil on one or both sides of a prepreg obtained by stacking two or more prepregs of the present invention, and then molding the laminate under heat and pressure.

[0149] The metal of the metal foil is not particularly limited as long as it is used for electrical insulating material applications, but from the viewpoint of electrical conductivity, it is preferably copper, gold, silver, nickel, platinum, molybdenum, ruthenium, aluminum, tungsten, iron, titanium, chromium, or an alloy containing at least one of these metal elements, more preferably copper or aluminum, and most preferably copper.

[0150] The conditions for hot and pressure molding are not particularly limited, but for example, the temperature can be 100 to 300° C., the pressure can be 0.2 to 10.0 MPa, and the time can be 0.1 to 5 hours. In addition, the hot and pressure molding can be performed using a vacuum press or the like to maintain a vacuum state for 0.5 to 5 hours.

[0151] The multilayer printed wiring board of the present invention is a multilayer printed wiring board containing the prepreg or laminate of the present invention. That is, the multilayer printed wiring board of the present invention can be manufactured by hot-press molding the prepreg or laminate of the present invention. The conditions of hot-press molding are not particularly limited, and the same conditions as those described above can be adopted. The multilayer printed wiring board of the present invention can be manufactured, for example, by subjecting the prepreg obtained by the method for producing the prepreg of the present invention or the laminate obtained by the method for producing the laminate of the present invention to circuit formation processing and multilayer adhesion processing. Examples of the method for circuit formation processing include known methods, that is, methods for circuit formation processing by drilling, metal plating, etching of metal foil, etc.

[0152] [Semiconductor package] The present invention also provides a semiconductor package including the printed wiring board, more specifically, a semiconductor package including a semiconductor element mounted on the printed wiring board. The semiconductor package of this embodiment can be manufactured by mounting a semiconductor element such as a semiconductor chip or memory at a predetermined position on the printed wiring board and sealing the semiconductor element with a sealing resin or the like.

[0153] Although the preferred embodiments of the present invention have been described above, these are merely examples for the purpose of explaining the present invention, and it is not intended that the scope of the present invention be limited only to these embodiments. The present invention can be embodied in various forms different from the above-described embodiment without departing from the spirit and scope of the present invention. EXAMPLES

[0154] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples.

[0155] [Production of polyphenylene ether derivative (A)] According to the following procedure and the compounding amounts in Table 1, a polyphenylene ether derivative (A) was produced.

[0156] (Production Example A-1: ​​Production of polyphenylene ether derivative (A-1)) Toluene, polyphenylene ether having a number average molecular weight of about 16,000, and p-aminophenol were placed in a 2 L glass flask equipped with a thermometer, a reflux condenser, and a stirrer, and dissolved with stirring at 90°C. After visually confirming that the solution had dissolved, t-butylperoxyisopropyl monocarbonate and manganese naphthenate were added and the solution was allowed to react at a temperature of 90°C for 4 hours, after which it was cooled to 70°C to obtain a polyphenylene ether compound (A'') having primary amino groups at the molecular terminals. A small amount of the reaction solution was taken out and measured by gel permeation chromatography (GPC). As a result, the peak derived from p-aminophenol disappeared, and the number average molecular weight of the polyphenylene ether compound (A'') was about 9,200. In addition, a small amount of the reaction solution was dropped into a methanol / benzene mixed solvent (mixed mass ratio: 1 / 1) to reprecipitate and FT-IR measurement of the purified solid content (reaction product) showed an average peak height of 3,400 cm -1 The appearance of a peak derived from a primary amino group in the vicinity was confirmed.

[0157] Here, the number average molecular weight was calculated from a calibration curve using standard polystyrene by gel permeation chromatography (GPC). The calibration curve was approximated by a cubic equation using standard polystyrene: TSKstandard POLYSTYRENE (Type; A-2500, A-5000, F-1, F-2, F-4, F-10, F-20, F-40) [manufactured by Tosoh Corporation, product name]. The measurement conditions for GPC are shown below. Device: Pump: L-6200 type [manufactured by Hitachi High-Technologies Corporation] Detector: L-3300 type RI [Hitachi High-Technologies Corporation] Column oven: L-655A-52 [Hitachi High-Technologies Corporation] Column: Guard column: TSK Guardcolumn HHR-L + Column: TSKgel G4000HHR + TSKgel G2000HHR [all manufactured by Tosoh Corporation, product names] Column size: 6.0 x 40 mm (guard column), 7.8 x 300 mm (column) Eluent: Tetrahydrofuran Sample concentration: 30mg / 5mL Injection volume: 20μL Flow rate: 1.00mL / min Measurement temperature: 40℃

[0158] Next, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide (BMI-5100 (trade name), manufactured by Daiwa Chemical Industry Co., Ltd.) and propylene glycol monomethyl ether were added to the above reaction solution, and the liquid temperature was raised with stirring. The mixture was reacted for 4 hours while maintaining the temperature at 120°C, and then cooled and filtered through a 200 mesh filter to produce a polyphenylene ether derivative (A-1).

[0159] A small amount of this reaction solution was taken and reprecipitated in the same manner as above. The purified solid was subjected to FT-IR measurement, and -1 The disappearance of the peak due to the primary amino group in the vicinity of 1,700 to 1,730 cm -1 The appearance of a peak derived from the carbonyl group of maleimide was confirmed. Furthermore, when this solid was subjected to GPC (under the same conditions as above), the number average molecular weight was found to be about 9,400.

[0160] (Production Examples A-2 to A-3: Production of Polyphenylene Ether Derivatives (A-2) to (A-3)) Polyphenylene ether derivatives (A-2) to (A-3) were produced in the same manner as in Production Example A-1, except that the raw materials and the amounts of each were changed as shown in Table 1. The number average molecular weights of the polyphenylene ether derivatives (A-2) to (A-3) are shown in Table 1.

[0161] [Table 1]

[0162] The abbreviations for each material in Table 1 are as follows. (1) Polyphenylene ether PPO640: Polyphenylene ether, number average molecular weight = approx. 16,000, trade name (manufactured by SABIC Innovative Plastics) (2) Aminophenol compounds (VIII) p-Aminophenol: Ihara Chemical Industry Co., Ltd. m-Aminophenol: Kanto Chemical Co., Ltd. (3) Bismaleimide compounds (IX) BMI-5100: 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, trade name (manufactured by Daiwa Chemical Industry Co., Ltd.) BMI-4000: 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, trade name (manufactured by Daiwa Chemical Industry Co., Ltd.) BMI-TMH: 1,6-bismaleimide-(2,2,4-trimethyl)hexane, trade name (manufactured by Daiwa Chemical Industry Co., Ltd.) (4) Reaction catalyst Perbutyl (registered trademark) I: t-butylperoxyisopropyl monocarbonate (manufactured by NOF Corporation) Manganese naphthenate (manufactured by Wako Pure Chemical Industries, Ltd.) (5) Organic Solvent Toluene (Kanto Chemical Co., Ltd.) Propylene glycol monomethyl ether (Kanto Chemical Co., Ltd.)

[0163] [Production of aminobismaleimide compounds (C-1) to (C-3) and phenol-modified cyanate prepolymer (C-4)] According to the procedure below and the compounding amounts in Table 2, the aminobismaleimide compounds (C-1) to (C-3) and the phenol-modified cyanate prepolymer (C-4), which are thermosetting resins, were produced.

[0164] [Production Example C-1: Production of aminobismaleimide compound (C-1)] 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane and propylene glycol monomethyl ether were charged into a 1 L glass flask equipped with a thermometer, a reflux condenser, and a stirrer, which was capable of being heated and cooled, and the mixture was reacted for 3 hours with stirring while maintaining the liquid temperature at 120°C. The mixture was then cooled and filtered through a 200 mesh filter to produce aminobismaleimide compound (C-1).

[0165] [Production Examples C-2 to C-3: Production of Aminobismaleimide Compounds (C-2) to (C-3)] Aminobismaleimide compounds (C-2) to (C-3) were produced in the same manner as in Production Example C-1, except that the raw materials and their amounts in each were changed as shown in Table 2.

[0166] [Production Example C-4: Production of Phenol-Modified Cyanate Prepolymer (C-4)] Toluene, 2,2-bis(4-cyanatophenyl)propane, and p-(α-cumyl)phenol were added to a 1 L glass flask equipped with a thermometer, a reflux condenser, and a stirrer, and after visually confirming that they had dissolved, manganese naphthenate was added as a reaction catalyst while stirring, while maintaining the liquid temperature at 110°C, and the reaction was carried out for 3 hours. After that, the mixture was cooled and filtered through a 200 mesh filter to produce a phenol-modified cyanate prepolymer (C-4).

[0167] [Table 2]

[0168] The abbreviations for each material in Table 2 are as follows. (1) Maleimide compound (a) BMI-5100: 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, trade name (manufactured by Daiwa Chemical Industry Co., Ltd.) BMI-4000: 2,2-bis(4-(4-maleimidophenoxy)phenyl)propane, trade name (manufactured by Daiwa Chemical Industry Co., Ltd.) (2) Aromatic diamine compound (b) BAPP: 2,2-bis(4-(4-aminophenoxy)phenyl)propane, trade name (manufactured by Wakayama Seika Kogyo Co., Ltd.) Bisaniline-P: 4,4'-[1,4-phenylenebis(1-methylethylidene)]bisaniline, trade name (manufactured by Mitsui Chemicals, Inc.) Bisaniline-M: 4,4'-[1,3-phenylenebis(1-methylethylidene)]bisaniline, trade name (manufactured by Mitsui Chemicals, Inc.) (3) Cyanate resin BADCy: Primaset® BADCy, 2,2-bis(4-cyanatophenyl)propane (Lonza) (4) Monophenolic compounds p-(α-cumyl)phenol (Mitsui Fine Chemicals Co., Ltd.) (5) Reaction catalyst Manganese naphthenate (manufactured by Wako Pure Chemical Industries, Ltd.) (6) Organic Solvents Toluene (Kanto Chemical Co., Ltd.) Propylene glycol monomethyl ether (Kanto Chemical Co., Ltd.)

[0169] [Examples 1 to 21 and Comparative Examples 1 to 17; Preparation of Resin Compositions] Each component shown in Tables 3 and 4 was stirred and mixed while heating at room temperature or from 50 to 80°C in the amounts (unit: parts by mass) shown in Tables 3 and 4 to prepare a resin composition having the solid content concentration shown in Tables 3 and 4. Here, the amount of inorganic filler to be mixed is usually set so that the density of the resin composition (excluding the inorganic filler) is 1.20 to 1.25 g / cm. 3 The density of the inorganic filler used is 2.2 to 3.01 g / cm 3 Therefore, when 160 parts by mass of the inorganic filler is mixed with 100 parts by mass of the resin composition (excluding the inorganic filler), the content is about 39 to 48% by volume. The raw materials and intermediate products used in the above production examples are either in trace amounts or deactivated, and even if they remain in the resin composition, they can be ignored.

[0170] [Evaluation and measurement methods] Using the resin compositions obtained in the Examples and Comparative Examples, prepregs and copper-clad laminates were produced according to the following methods, and measurements and evaluations were carried out using them. The results are shown in Tables 5 to 6. The results of Examples 1 to 21 and Comparative Examples 1 to 17 in Tables 5 to 6 are the measurement and evaluation results of the compositions prepared in Preparation Examples 1 to 21 and Comparative Preparation Examples 1 to 17 in Tables 3 and 5, respectively.

[0171] (Preparation of prepregs and copper-clad laminates) The resin composition obtained in each example was applied to a 0.1 mm thick glass cloth (E glass, manufactured by Nitto Boseki Co., Ltd.), and then heated and dried at 160°C for 7 minutes to produce a prepreg with a resin composition content (including organic solvent) of approximately 54 mass%. Six of these prepregs were stacked, and 18 μm thick low-profile copper foil (FV-WS, M side Rz: 1.5 μm, manufactured by Furukawa Electric Co., Ltd.) was placed on top and bottom with the M side in contact, and heated and pressurized at a temperature of 230°C, a pressure of 3.9 MPa, and a time of 180 minutes to produce a double-sided copper-clad laminate (thickness: 0.8 mm).

[0172] (Appearance evaluation of prepreg) The appearance of the prepreg obtained above was observed and evaluated visually according to the following criteria. A: There is no visible abnormality. C: The prepreg surface has some unevenness, streaks, foaming, phase separation, etc., and the surface lacks smoothness.

[0173] (Measurement of outgassing amount of prepreg) First, the mass of the prepreg (prepreg before heat treatment) produced in each example was measured. Next, the mass of the prepreg (prepreg after heat treatment) after heat treatment at a temperature of 163° C. for 15 minutes was measured. From these measured values, the amount of outgassing of the prepreg was calculated using the following formula. Outgassing amount (mass%)={(mass of prepreg before heat treatment-mass of prepreg after heat treatment) / mass of prepreg before heat treatment}×100

[0174] (Evaluation of copper clad laminate properties) The copper-clad laminate obtained above was evaluated for high frequency characteristics, copper foil peel strength, glass transition temperature, thermal expansion coefficient, solder heat resistance, and flame retardancy. The method for evaluating the properties of the copper-clad laminate was as follows.

[0175] (1) High-frequency characteristics After etching away the copper foil on both sides of the copper-clad laminate, the laminate was cut into a size of 60 mm x 2 mm and dried at 105°C / hr to prepare a test piece. Dk and Df at 10 GHz were calculated from the resonance frequency and unloaded Q value obtained by the cavity resonator method. The measurements were performed at an ambient temperature of 25° C. using an Agilent Technologies vector network analyzer E8364B, a Kanto Electronics Application Development CP531 (10 GHz resonator) and a CPMA-V2 (program). (2) Copper foil peel strength The adhesion to the conductor was measured in accordance with JIS C6481 (1996). (3) Solder heat resistance (moisture absorption and heat resistance) Using 50mm square test pieces with the copper foil on both sides of the copper-clad laminate etched, the test pieces were treated in the normal state and in a pressure cooker test (PCT) device (conditions: 121°C, 2.2 atm) for a specified time (1 hour, 3 hours, and 5 hours), and then immersed in molten solder at 288°C for 20 seconds, and the appearance of the test pieces after solder immersion was visually observed. The numbers in the table indicate the number of test pieces out of three after solder immersion that showed no abnormalities such as swelling or measling. (4) Glass transition temperature (Tg) and thermal expansion coefficient The glass transition temperature (Tg) and thermal expansion coefficient (linear expansion coefficient) were measured in the plate thickness direction [Z direction], temperature range: 30 to 150°C using 5 mm square test pieces with copper foil etched on both sides using a thermomechanical analyzer (TMA) [Model Q400, manufactured by TA Instruments Japan, Inc.] in accordance with the IPC (The Institute for Interconnecting and Packaging Electronic Circuits) standard. (5) Flame retardancy The copper-clad laminate was immersed in a 10% by mass solution of ammonium persulfate (manufactured by Mitsubishi Gas Chemical Company, Inc.), which is a copper etching solution, to remove the copper foil. From the resultant evaluation board, test pieces 127 mm in length and 12.7 mm in width were cut out, and the flame retardancy of the test pieces was tested and evaluated in accordance with the UL94 test method (Method V). That is, the lower end of the test piece was held vertically and exposed to a 20 mm flame for 10 seconds twice. The evaluation was performed according to the UL94 V method standard.

[0176] [Table 3]

[0177] [Table 4]

[0178] The abbreviations for each material in Tables 4 and 5 are as follows: (1) Polyphenylene ether derivatives A-1: The polyphenylene ether derivative (A-1) obtained in Production Example (A-1) was adjusted to the solids concentration shown in the table by removing the organic solvent or adding toluene and propylene glycol monomethyl ether as appropriate. A-2: The polyphenylene ether derivative (A-2) obtained in Production Example (A-2) was adjusted to the solids concentration shown in the table by removing the organic solvent or adding toluene and propylene glycol monomethyl ether, as appropriate. A-3: The polyphenylene ether derivative (A-3) obtained in Production Example (A-3) was adjusted to the solids concentration shown in the table by removing the organic solvent or adding toluene and propylene glycol monomethyl ether as appropriate.

[0179] (2) Curing accelerator (B) <Organized oxide> Perbutyl (registered trademark) P: α,α'-bis(t-butylperoxy)diisopropylbenzene, trade name (manufactured by NOF Corporation), 1-minute half-life temperature 175.4°C Percumyl (registered trademark) D: bis(1-phenyl-1-methylethyl) peroxide, trade name (manufactured by NOF Corporation), 1-minute half-life temperature 175.2°C Percumyl (registered trademark) P: diisopropylbenzene hydroperoxide, trade name (manufactured by NOF Corporation), 1-minute half-life temperature 232.5°C <Imidazole-based curing agent> G-8009L: Isocyanate masked imidazole (addition product of hexamethylene diisocyanate resin and 2-ethyl-4-methylimidazole), trade name (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 2MZ-H: 2-Methylimidazole, trade name (manufactured by Shikoku Kasei Co., Ltd.) 2E4MZ: 2-ethyl-4-methylimidazole, trade name (manufactured by Shikoku Kasei Co., Ltd.) ·1B2MZ: 1-benzyl-2-methylimidazole, trade name (manufactured by Shikoku Kasei Co., Ltd.) ·C11Z: 2-undecylimidazole, trade name (manufactured by Shikoku Kasei Co., Ltd.) 2MA-OK: 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, trade name (manufactured by Shikoku Kasei Co., Ltd.) <Phosphorus-based curing accelerator> TPP-MK: Tetraphenylphosphonium, product name (manufactured by Hokko Sangyo Co., Ltd.) TPP-S: Triphenylphosphonium, product name (manufactured by Hokko Sangyo Co., Ltd.)

[0180] (3) Thermosetting resin (C) C-1: The aminobismaleimide compound (C-1) obtained in Production Example (C-1) is adjusted to the solids concentration shown in the table by removing the organic solvent or adding propylene glycol monomethyl ether as appropriate. C-2: The aminobismaleimide compound (C-2) obtained in Production Example (C-2) is adjusted to the solids concentration shown in the table by removing the organic solvent or adding propylene glycol monomethyl ether as appropriate. C-3: The aminobismaleimide compound (C-3) obtained in Production Example (C-3) was adjusted to the solids concentration shown in the table by removing the organic solvent or adding propylene glycol monomethyl ether as appropriate. C-4: The phenol-modified cyanate prepolymer (C-4) obtained in Production Example (C-4) was adjusted to the solids concentration shown in the table by removing the organic solvent or adding toluene as appropriate. NC-7000L: naphthol novolac type epoxy resin, product name (manufactured by Nippon Kayaku Co., Ltd.)

[0181] (4) Inorganic filler (D) SO-C2: Spherical fused silica, average particle size: 0.5 μm, density: 2.2 g / cm 3 , Product name (manufactured by Admatechs Co., Ltd.)

[0182] (5) Flame retardants (E) OP-930: aluminum dialkylphosphinic acid salt, metal salt of disubstituted phosphinic acid, phosphorus content: 23.5% by mass, trade name (manufactured by Clariant) HCA-HQ: 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, cyclic organic phosphorus compound, phosphorus content: 9.6% by mass, trade name (manufactured by Sanko Co., Ltd.)

[0183] [Table 5]

[0184] [Table 6]

[0185] Examples 1 to 16 are examples using a resin composition containing a polyphenylene ether derivative (A) and at least one curing accelerator (B) selected from the group consisting of an organic peroxide, an imidazole-based curing accelerator, and a phosphorus-based curing accelerator. Comparing the laminates of Examples 1 to 12 with Comparative Examples 1 to 12 described later, the laminates of Examples 1 to 12 have excellent high-frequency characteristics (particularly, dielectric tangent at 10 GHz), and further have good moisture absorption and heat resistance, adhesion to conductors, glass transition temperature, thermal expansion characteristics, and flame retardancy in a well-balanced manner. In particular, it is found that the solid content concentration in the resin composition has an effect on the high-frequency characteristics.

[0186] Examples 17 to 21 are examples using a resin composition containing a polyphenylene ether derivative (A) but not containing the curing accelerator (B). Comparing Examples 17 to 21 with Comparative Examples 13 to 17, it is found that the high frequency characteristics (particularly the dielectric tangent at 10 GHz) are excellent, and the influence of the solid content concentration in the resin composition is apparent. [Industrial Applicability]

[0187] The prepreg and resin composition of the present invention can exhibit high adhesion to conductors, excellent heat resistance, a high glass transition temperature, a low coefficient of thermal expansion, flame retardancy, and stable and excellent high-frequency characteristics (dielectric characteristics in the high-frequency band). The prepreg and laminates containing the prepreg can be suitably used for electronic parts applications such as multilayer printed wiring boards and semiconductor packages.

Claims

1. A prepreg comprising a resin composition and a sheet-like fiber reinforcing substrate, the resin composition comprising a polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group, A prepreg in which the amount of outgassing generated when heated at a temperature of 163°C for 15 minutes is 0.67 mass% or less based on the entire prepreg.

2. 2. The prepreg according to claim 1, wherein the outgassing amount is 0.65 mass% or less based on the entire prepreg.

3. 3. The prepreg according to claim 1 or 2, wherein the N-substituted maleimide structure-containing group is a group containing a bismaleimide structure in which nitrogen atoms of two maleimide groups are bonded to each other via an organic group.

4. The prepreg according to any one of claims 1 to 3, wherein the N-substituted maleimide structure-containing group is a group represented by the following general formula (Z): 【Chemistry 1】 (In the formula, R 2 are each independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and y is an integer of 0 to 4. 1 is a group represented by the following general formula (II), (III), (IV) or (V): 【Chemistry 2】 (In the formula, R 3 are each independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom; and p is an integer of 0 to 4. 【Chemistry 3】 (In the formula, R 4 and R 5 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 2 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a single bond, or a group represented by the following general formula (III-1): q and r each independently represent an integer of 0 to 4. 【Chemistry 4】 (In the formula, R 6 and R 7 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 3 is an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond; s and t each independently are an integer of 0 to 4. 【Chemistry 5】 (In the formula, n is an integer from 0 to 10.) 【Chemistry 6】 (In the formula, R 8 and R 9 are each independently a hydrogen atom or an aliphatic hydrocarbon group having 1 to 5 carbon atoms; and u is an integer of 1 to 8.

5. The prepreg according to any one of claims 1 to 4, wherein the resin composition further contains at least one curing accelerator (B) selected from the group consisting of organic peroxides, imidazole-based curing accelerators, and phosphorus-based curing accelerators.

6. The prepreg according to any one of claims 1 to 5, wherein the resin composition further contains at least one thermosetting resin (C) selected from the group consisting of epoxy resins, cyanate resins, and maleimide compounds.

7. The prepreg according to claim 6, wherein the maleimide compound in the thermosetting resin (C) comprises at least one selected from the group consisting of a maleimide compound (a) having at least two N-substituted maleimide structure-containing groups and an aminobismaleimide compound (c) represented by the following general formula (VI): 【Chemistry 7】 (In the formula, A 4 is A in the general formula (Z) described in claim 4. 1 The definition is the same as that of A 5 is a group represented by the following general formula (VII): 【Chemistry 8】 (In the formula, R 17 and R 18 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, a hydroxyl group, or a halogen atom. 8 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a fluorenylene group, a single bond, or a group represented by the following general formula (VII-1) or (VII-2). q' and r' each independently represent an integer of 0 to 4. 【Chemistry 9】 (In the formula, R 19 and R 20 Each of A is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 9 is an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an m- or p-phenylenediisopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. s' and t' each independently represent an integer of 0 to 4. 【Chemistry 10】 (In the formula, R 21 is an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. 10 and A 11 are each independently an alkylene group having 1 to 5 carbon atoms, an isopropylidene group, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond; and w is an integer of 0 to 4.

8. A laminate comprising the prepreg according to any one of claims 1 to 7 and a metal foil.

9. A multilayer printed wiring board comprising the prepreg according to any one of claims 1 to 7 or the laminate according to claim 8.

10. A semiconductor package comprising the multilayer printed wiring board according to claim 9 and a semiconductor element mounted thereon.

11. A method for producing a prepreg, comprising impregnating or coating a sheet-like fiber-reinforced substrate with a resin composition and drying the substrate to produce a prepreg, the resin composition containing a polyphenylene ether derivative (A) having an N-substituted maleimide structure-containing group and an organic solvent, and comprising a step (X) of treating the prepreg so that the amount of outgassing is such that the prepreg satisfies the following condition, the step (X) comprising a step of adjusting the solids concentration of the resin composition to 55.0 to 80 mass %. (Conditions for outgassing amount) The amount of outgassing generated when heated at a temperature of 163° C. for 15 minutes is 0.67 mass % or less based on the entire prepreg.

12. A method for producing a laminate, comprising laminating a prepreg obtained by the method for producing a prepreg according to claim 11 and a metal foil, and applying heat and pressure by a pressing method.

13. A method for producing a multilayer printed wiring board, comprising subjecting a prepreg obtained by the method for producing a prepreg according to claim 11 or a laminate obtained by the method for producing a laminate according to claim 12 to a circuit formation process and a multilayer adhesive process.

Citation Information

Patent Citations

  • Laminated board and its molding method

    JP1983069046A

  • Lighting device of industrial telecamera

    JP1986018937A

  • Thermosetting resin composition of semi-IPN-type compound material, and varnish, prepreg and metal-clad laminate board using the same

    JP2008095061A

  • Thermosetting insulating resin composition, and prepreg, film with resin, laminate and multilayer printed wiring board using the same

    JP2010043254A

  • Thermosetting resin composition, and prepreg, laminate and printed wiring board using the same

    JP2014019796A